Spatiotemporal Baltic Sea area 16S metabarcoding from three projects performed in 2015-2017 (+storage test 2019) - Krzysztof Jurdzinski (Royal Institute of Technology, 2025)
The 16S (V3–V4) metabarcoding results presented here are described in detail in our manuscript (http://biorxiv.org/content/10.1101/2024.08.14.607742) and originate from the following sampling efforts: 1. Bi-weekly sampling along the Swedish marine monitoring program across twelve locations in Baltic Proper, Kattegat, and Skagerrak. For all the locations, sampling was performed between February 2016 and March 2017. Additionally, one station (Släggö, Skagerrak) was sampled from August 2015.2. Weekly sampling at multiple depths (5, 10, and 15 meters in most cases) at Tångesund, Sweden (Skagerrak), performed in 2016 between August 22nd and October 10th.3. Three longitudinal transects in Skagerrak, performed in 2016 on August 18th, 4. Replicate samples collected at Släggö marine station (Skagerrak) on the same date (August 20th 2019) and stored as filters before DNA extraction for 1 week, 1 month, 3 months, or 6 months, in either -20⁰C or -80⁰C.The extracted DNA was stored at -20⁰C until mid-2023 when the amplicon sequencing was performed. All the contextual data has been obtained from the SharkWeb portal maintained by the Swedish Meteorological and Hydrological Institute.

This dataset was published via the SBDI ASV portal (https://asv-portal.biodiversitydata.se/) , and has been updated from 'Metadata only' to 'Occurrence' type.
Keywords: Metadata; Observation; OCCURRENCE; Biological Sciences; Biologi